A systematic review of the safety and effectiveness of repetitive transcranial magnetic stimulation in the treatment of peripartum depression. (August 2019) - Cole, Jaeden; Bright, Katherine; Gagnon, Lisa; McGirr, Alexander
Abstract: Background: Repetitive Transcranial Magnetic Stimulation (rTMS) is an efficacious treatment for major depressive disorder (MDD), however there is limited safety and efficacy data in the peripartum period. The purpose of this review is to systematically examine the safety, acceptability and effectiveness of rTMS administered during the peripartum period as an intervention for MDD. Methods: We searched MEDLINE, EMBASE and PsychINFO from 2008 to January 2019 to identify peer reviewed publications evaluating rTMS during the peripartum period as an intervention for peripartum MDD. We systematically extracted reported adverse events, side effects, rates of discontinuation, as well as clinical response and remission. Results: Data was synthesized from 1 randomized control trial, 3 uncontrolled trials, 3 case series and 5 case studies, representing a total of 87 patients. No serious adverse events were reported. Side effects occurred at rates comparable to those observed in the non-peripartum population, and obstetric and neonatal complications are infrequent and do not separate from sham-rTMS. Randomized controlled data suggests antidepressant efficacy with an effect size of 0.87. Uncontrolled studies report rates of clinical response between 41.4% and 71.4%, and rates of clinical remission between 20.7 and 30.0%. The treatment appears acceptable, with few patients opting to discontinue treatment. Limitations: Due to the paucity of research in this population, majority of data comes from sources with inherently higher risk of bias. Conclusions: rTMS in the peripartum period appears to be efficacious, acceptable and well tolerated. Additional research is required, however rTMS's risk benefit profile may be attractive to women in the peripartum period. Highlights: Systematic review of peer reviewed reports of rTMS to treat peripartum depression. Data was synthesized from 87 women who received rTMS for peripartum depression. rTMS appears effective at alleviating depressive symptoms in the peripartum period. No serious adverse events were reported with rTMS used during the peripartum period. rTMS in peripartum depression appears acceptable, with few patient drop-outs.